Neutrophil NETworking in ENL: Potential as a Putative Biomarker: Future Insights - Sahu, Smrity; Sharma, Keshav; Sharma, Maryada; Narang, Tarun; Dogra, Sunil; Minz, Ranjana Walker; Chhabra, Seema (Frontiers in Medicine, 2021)
Erythema nodosum leprosum (ENL) is an immune- complex mediated state encountered in patients with borderline lepromatous and lepromatous leprosy. The consequences of ENL may be serious, leading to permanent deformities.. The management of ENL is challenging due to chronic, recurrent nature of disease, neuritis, and organ involvement and necessitates prolonged treatment with prednisolone, thalidomide, and immunosuppressive drugs, which further adds to the existing morbidity. In addition, use of these therapies carry a risk of reactivation of persisters (Mycobacterium leprae), apart from their end-organ toxicities. It is difficult to predict which patients will develop chronic or recurrent ENL and plan the treatment according to the patient profile. We need simple tests which can help us in identifying patients who are likely to require prolonged treatment and also inform us about the prognosis of reactions so that appropriate therapy may be started and continued for better disease control. There is a significant unmet research need for better understanding the immunopathogenesis of and biomarkers for ENL to improve clinical stratification and therapeutics. In this review we will discuss the potential of neutrophils as putative biomarkers by virtue of their universal abundance in human blood, functional versatility, heterogeneity, plasticity, differential hierarchical cytoplasmic granule mobilization, and ability to form neutrophil-extracellular-traps. We also hypothesize about an element of metabolic reprogramming of neutrophils by Mycobacterium leprae that could be investigated and exploited. In the end, a potential role for neutrophil derived exosomes as a novel biomarker for ENL will also be explored.